Electronic Information Interception from the Perspectives of Positive Law and Islamic Criminal Law: A Multicultural Study on Privacy Protection in Indonesia - Ubaidillah, M. Hasan (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2025)
The criminal offense of interception of electronic information constitutes a violation of privacy rights in digital communication as regulated in Indonesian positive law, particularly in the Information and Electronic Transaction Law (ITE Law). Illegal interception, or wiretapping without authorization, can result in violations of human rights and entail legal consequences for the perpetrator. From the perspective of Islamic criminal law, this action can also be categorized as an act that violates principles of justice, protection of individual honor, and the prohibition of tajassus (spying) as mentioned in the Qur'an and hadith. This research analyzes regulations regarding interception in Indonesian positive law and reviews their conformity with the principles of Islamic criminal law. Furthermore, this research also examines the implementation of these regulations in the context of Indonesia's multicultural society, which consists of diverse religions, ethnicities, and cultures, in order to assess the extent to which law enforcement can guarantee justice and protection of privacy rights for all levels of society. The findings indicate that both positive law and Islamic law equally emphasize protection of individual privacy rights and provide sanctions for parties who violate these rules. Therefore, there is a need for strengthening of regulations and oversight mechanisms to ensure that interception actions are only conducted within the limits permitted by law and for legitimate purposes, such as law enforcement and state security.